Chlamydia trachomatis perturbs antigen cross presentation by interfering Rab14- controlled transport - del Balzo, Diego Damián (2018)
Chlamydia trachomatis (Ct) is the most common sexually transmitted bacterium that replicates inside a vesicle called inclusion. Ct manipulatesRab GTPases, master controllers of vesicular transport, to ensure its survival and replication. Dendritic cells (DC) are the most powerful antigenpresenting cells and an essential link between innate and adaptive immunity. We have shown that Ct intercepts Rab14-vesicles to acquire hostlipids necessary for its growth and multiplication. In addition, DC requires Insulin-regulated aminopeptidase (IRAP)-Rab14 endosomes forefficient antigen cross presentation. We hypothesised that Ct recruits Rab14 not only as a strategy for nourishment, but also to interfere withantigen presentation. By confocal microscopy, we observed that Rab14 is associated with the plasma membrane at the entry site of the bacterium.Later, Rab14 is recruited to the chlamydial inclusion membrane and remains there throughout the entire bacterial life cycle. Interestingly, wedistinguished two populations of chlamydial inclusions in DC. On one hand, we found small Ct-containing vesicles that colocalize with EEA1 orLAMP1; and on the other hand, we observed larger ones that recruit Rab14 and exclude markers from the endocytic/degradative pathway.Chlamydial infection did not modify MHC-I expression, shown by western blot. However, infection as well as Rab14 silencing caused aredistribution of MHC-I molecules and interfered with their transport towards the plasma membrane, assessed by flow cytometry. Our resultssuggest that Rab14 is involved in the decrease of antigen cross presentation observed in Ct-infected cells.